2009
DOI: 10.1007/s10522-009-9229-z
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Klotho KL-VS polymorphism in a large Italian population, from young subjects to centenarians, suggests the presence of specific time windows for its effect

Abstract: In mice a defect of Klotho gene expression results in multiple aging-like phenotypes including short lifespan, osteoporosis and atherosclerosis, while its over-expression suppresses aging and extends lifespan. Contrasting data have been reported as far as the importance of the functional variant of Klotho termed "KL-VS" on human longevity, depending on the average age of the old subjects that were compared with young controls. We therefore performed a study on a large Italian population sample including people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 32 publications
9
46
0
1
Order By: Relevance
“…The authors concluded that, "large differences in allele frequencies were not observed between ethnically and or geographically diverse populations for a given age group," However, our patients were younger than in the aforementioned study. In a study performed on a large Italian population sample, Invidia et al [28] reported a higher frequency of carrier of VV genotype (2.6%) in an age group similar to that of our patients group. We believe that the lack of evidence of F352 polymorphism effect on BMD and IMT measurements observed in our study is much more likely a result of the small sample size, rather than from differences in the allele frequency.…”
Section: Discussionsupporting
confidence: 86%
“…The authors concluded that, "large differences in allele frequencies were not observed between ethnically and or geographically diverse populations for a given age group," However, our patients were younger than in the aforementioned study. In a study performed on a large Italian population sample, Invidia et al [28] reported a higher frequency of carrier of VV genotype (2.6%) in an age group similar to that of our patients group. We believe that the lack of evidence of F352 polymorphism effect on BMD and IMT measurements observed in our study is much more likely a result of the small sample size, rather than from differences in the allele frequency.…”
Section: Discussionsupporting
confidence: 86%
“…We regard this result as very important, particularly in relation to the many results recently obtained in genetics. All the data collected in this and other studies suggest that, as well as a variety of nuclear DNA polymorphisms (Di Bona et al 2009;Gravina et al 2009;Invidia et al 2010;Lescai, Marchegiani, and Franceschi 2009;Salvioli et al 2006;Testa et al 2009), maternally inherited mitochondrial DNA variants (Capri et al 2008;Raule et al 2007;Rose et al 2007;Rose et al 2010;Santoro et al 2006) contribute substantially to human longevity too.…”
Section: Some Preliminary Resultsmentioning
confidence: 56%
“…Changes in KL gene expression would, over time, impact normal function of all downstream pathways. Evidence of such an effect is observed in the KL polymorphism KL VS (Arking et al 2002) where slight changes in KL function increases risk of disease (Arking et al 2002(Arking et al , 2003(Arking et al , 2005Invidia et al 2010;Wolf et al 2010). Of course, the overall contribution of a small change in one gene would not induce a dramatic phenotype in humans as it does in the KL knockout mouse; however, small changes in KL and numerous other genes would add up over time.…”
Section: Many Small Changes Can Affect Gene Expressionmentioning
confidence: 99%